2000
DOI: 10.1128/jb.182.23.6565-6569.2000
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of 4-Hydroxyacetophenone into 4-Phenyl Acetate by a Flavin Adenine Dinucleotide-Containing Baeyer-Villiger-Type Monooxygenase

Abstract: An arylketone monooxygenase was purified from Pseudomonas putida JD1 by ion exchange and affinity chromatography. It had the characteristics of a Baeyer-Villiger-type monooxygenase and converted its substrate, 4-hydroxyacetophenone, into 4-hydroxyphenyl acetate with the consumption of one molecule of oxygen and oxidation of one molecule of NADPH per molecule of substrate. The enzyme was a monomer with an M r of about 70,000 and contained one molecule of flavin adenine dinucleotide (FAD). The enzyme was specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
25
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…(11,12); a novel 4-hydroxyacetophenone monooxygenase from two Pseudomonas spp. (37,65); and CHMO activities from a black yeast (29) and the fungus Cunninghamella echinulata (3). To date, the complete pathway genes of only the cyclohexanol metabolism in Acinetobacter sp.…”
mentioning
confidence: 99%
“…(11,12); a novel 4-hydroxyacetophenone monooxygenase from two Pseudomonas spp. (37,65); and CHMO activities from a black yeast (29) and the fungus Cunninghamella echinulata (3). To date, the complete pathway genes of only the cyclohexanol metabolism in Acinetobacter sp.…”
mentioning
confidence: 99%
“…In Pseudomonas putida JD1, the aerobic p-ethylphenol degradation pathway is initiated by an oxygen-independent hydroxylation (9). However, subsequent reaction steps include monooxygenase activity (48), necessitating a different pathway under anoxic conditions.…”
mentioning
confidence: 99%
“…revealed high similarity in an internal part of the protein. 52 Purification, gene cloning, sequence analysis, and biochemical characterization of 4-hydroxyacetophenone monooxygenase (HAPMO) from P. fluorescens ACB was reported by the group of Janssen one year after purification of the aryl ketone MO. 49 Purified HAPMO was reported to be a FAD-containing homodimer of 140 kDa and significant similarities (∼33%) in the protein sequence were found with CHMO and SMO.…”
mentioning
confidence: 99%
“…strain 101 indicated three metabolic pathways, two of them involving enzymatic BV reactions. 136 The first aromatic ketone degrading enzyme to be purified was the aryl ketone MO from P. putida JD1, 52 a strain which was previously shown to be responsible for the conversion of aromatic ketones. 133 Biochemical characterization showed that the enzyme contains one molecule of FAD and has a molecular weight of M r ≈ 70 kDa.…”
mentioning
confidence: 99%